SPE International Symposium on Oilfield Chemistry 2011
DOI: 10.2118/141459-ms
|View full text |Cite
|
Sign up to set email alerts
|

Surface Energy of North American Shales and its Role in Interaction of Shale with Surfactants and Microemulsions

Abstract: In recent years a number of laboratory studies on the use of surfactants and microemulsions in hydraulic fracturing of shale formations have been reported. These studies mainly focused on such metrics as improvement in permeability regain and enhancement of fluid recovery from packed columns upon the use of surfactant-containing chemicals. Laboratory studies have also been backed by the documented observations from the field illustrating benefits of using microemulsions for the increase in gas production from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…This was attributed to increase in the adsorption of surfactant with hydrophobic tail facing the shale rock surface. 30 Similarly, another investigation on wettability of Bakken shale using both anionic and nonionic surfactant solutions found that wettability of the upper Bakken shale shifted from oil wet to neutral wet at 60 to 90 ℃ and for the middle Bakken it altered from weakly oil wet to neutral wet at 23 ℃. 3 The discrepancy between the above mentioned studies and the results in this study might be due differences in the mineralogy, pore types, the composition of crude oil, and measurement techniques.…”
Section: Wettability-surfactant Concentrationmentioning
confidence: 95%
“…This was attributed to increase in the adsorption of surfactant with hydrophobic tail facing the shale rock surface. 30 Similarly, another investigation on wettability of Bakken shale using both anionic and nonionic surfactant solutions found that wettability of the upper Bakken shale shifted from oil wet to neutral wet at 60 to 90 ℃ and for the middle Bakken it altered from weakly oil wet to neutral wet at 23 ℃. 3 The discrepancy between the above mentioned studies and the results in this study might be due differences in the mineralogy, pore types, the composition of crude oil, and measurement techniques.…”
Section: Wettability-surfactant Concentrationmentioning
confidence: 95%
“…Therefore, we expect low 499 surfactant losses due to adsorption on shale during hydraulic frac-500 turing with this surfactant. There are a number of experimental 501 studies that report a reduction in contact angle when using non-502 ionic surfactants with negatively charged surfaces such as quartz503 and shale[20,39,40]. The reduction in CA was attributed to (/g in[20]), which is three to four times smaller than the 510 adsorption of nonionic surfactant in these studies.…”
mentioning
confidence: 87%
“…Although the effect of some surfactants on the interfacial 38 properties of shale oil systems has been investigated in the past, the limited data available in the litera-39 ture were mainly obtained at ambient conditions and thus may not be representative of fluid-rock inter- 40 actions at actual reservoir conditions. 41 In this study, a new framework is proposed to investigate the effect of surfactants on fundamental 42 parameters governing fluid displacement in two brine/oil/shale systems (A and B) at reservoir conditions.…”
mentioning
confidence: 99%
“…Furthermore, we observed an increase in the contact angle for higher surfactant concentrations (up to 60 ppm): Shale surfaces treated with the surfactant are characterized by a high contact angles for deionized (DI) water (Figure 1), while spontaneous imbibition tests on neighboring samples demonstrate a reduced uptake of the surfactant solutions relative to pure water. Surface energy values obtained from contact angle measurements have been found to be similar for most shale types (Zelenev, 2011), which makes those measurements relatively ineffective in determining an optimal and field-specific treatment (surfactant). These observations are usually obtained from small samples, and due to the heterogeneous nature of shales, a good deal of variability (uncertainty) is associated with such measurements: Contact angle observations, as a result, can vary significantly even for samples that are located in close proximity.…”
Section: Introductionmentioning
confidence: 99%